Choosing the Best Investment Decision in San Luis Potosí Through Multicriteria Models - Izar Landeta, Juan Manuel; Nájera Saldaña, José Adrián; Zárate Camacho, Lizbeth Angélica (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To choose the best option among five, under 10 decision criteria, to make an investment in the city of San Luis Potosí using four multi-criteria decision models.MATERIAL AND METHOD: The weighting of the weights of the decision criteria has been carried out with Saaty's Hierarchical Prioritization Analysis and the multi-criteria decision models applied have been Moora, Topsis, Electre and Smart, which were used to classify the five decision options and see which of them is the best.RESULTS: The models did not agree regarding the best decision, since the first two give the investment in García Diego as the best decision, while the remaining two choose Torre Diamante.CONCLUSIONS: Even though there is no coincidence of the four models applied, it is obvious that the two best decision options are García Diego and Torre Diamante. This is an advantage that multi-criteria models provide over traditional project evaluation methods, which only consider quantitative aspects to choose the best project. With multi-criteria models, qualitative criteria are also included that consider the preferences of the decision-maker and arrive at a better decision.
Keywords: Decision options; Decision criteria; Multicriteria models; Decision matrix.